AN OVERVIEW ON THE USE OF THE SELENIUM (Se) IN AQUACULTURE - Lam, Ho Son; Sang, Huynh Minh (Vietnam Journal of Marine Science and Technology, 2018)
Effects of antibiotics usage in aquaculture on environment and human health has prompted the search for alternative products. Recently, the microelements in organic form have been used as alternative to antibiotics in aquaculture. Se is one of the microelements that have received heightened attention. This report reviews the role of Se in the culture of fishes (cobia Rachycentron canadum L., red sea bream Pagrus major, fingerling channel catfish Ictalurus punctatus, seabass Lates calcarifer, snubnose dart Trachinotus blochii, rainbow trout Oncorhynchus mykiss, common carp Cyprinus carpio L., Atlantic salmon parr Salmo salar, nile tilapia Oreochromis niloticus, african catfish Clarias gariepinus, Senegalese sole Solea senegalensis, grouper Epinephelus malabaricus, gilthead seabream Sparus aurata, Chinook salmon Oncorhynchus tshawytscha, fathead minnow Pimephales promelas, striped bass Morone saxatilis, bluegill Lepomis macrochirus, crucian carp Carassius auratus gibelio) and crustacean (giant freshwater prawn Macrobrachium rosenbergii, white shrimp Penaeus vannamei, marron Cherax cainii, crayfish Procambarus clarkii). Suggestion for further research on the application of Se in aquaculture is also included.